Digital Transformation and its Role in Enhancing the Security of Accounting Information An Analytical Study of the Opinions of a Sample of Accountants from Private Banks in Baghdad Governorate: Transformasi Digital dan Perannya dalam Meningkatkan Keamanan Informasi Akuntansi: Studi Analitis terhadap Pendapat Sebagian Akuntan dari Bank Swasta di Provinsi Baghdad - Lecturer.Dr. Jasim Mohammed Yaseen; Alaa Abd Al-hussen Omran Al-Zubaidi; Prof. Dr. Hikmat A. Alrawi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital transformation has become a central theme in modern organizations seeking to adapt to technological advancements and evolving operational environments. Specific Background This study focuses on the integration of digital transformation practices within organizational and financial systems, particularly in relation to performance and information security. Knowledge Gap Despite growing attention, limited clarity exists regarding how digital transformation interacts with organizational processes and performance outcomes in specific institutional contexts. Aims The study aims to examine the role of digital transformation in shaping organizational performance and supporting secure information systems. Results The findings indicate that digital transformation is associated with improved organizational processes, better data management, and stronger alignment with strategic objectives. Novelty The study offers a comprehensive perspective by linking digital transformation with both performance and information security considerations within organizations. Implications The results suggest that institutions should adopt structured digital strategies to optimize operational processes and ensure information security in dynamic environments. Keywords: Digital Transformation, Organizational Performance, Information Systems, Strategic Management, Information Security Key Findings Highlights Integration of technology supports structured operational processes Data management practices align with organizational objectives Security considerations are embedded within transformation strategies